Influence of concrete strength in the minimum shear reinforcement ratio of beams - González García, Sergio; Abd El Malik Shehata, Ibrahim; Domimgues Shehata, Lidia (Revista Ingeniería de Construcción, 2005)
Lightly reinforced concrete beams fail in a brittle manner, due to steel fracture soon after cracking of concrete. In order to avoid such a brittle failure and provide certain ductility at failure, codes of practice give formulae for minimum longitudinal and transverse reinforcement. This reinforcement is meant to resist loads beyond the first crack load and ensure that failure occur after the formation of several small cracks, improving the ductility of the beams. These design criteria are based mainly on empirical studies, and different code formulae lead to quite different amounts of minimum reinforcement, particularly for high strength concrete beams. In this work a theoretical and experimental investigation for the determination of the minimum shear steel ratio of concrete beams with different strength, having compared the formulae of different authors and code design is presented. The experimental program included tests on fourteen beams: seven of those were made of high strength concrete while the others seven had normal strength. Most of these beams had shear reinforcement in the wide range of variation of the minimum reinforcement proposed in the literature. It is also discussed which procedure would be the more appropriate for the determination of minimum shear steel ratio.